Mangrove ecosystems’ role in climate change mitigation - Ginalyn Cuenca-Ocay (Davao Research Journal)
Mangrove forests are crucial to ecosystems for their benefits, and role in climate change mitigation. Across marine and terrestrial boundaries, they shield coastal areas from tidal waves and storms, with dense roots that dissipate wave energy effectively. These roots also trap carbon-rich particles from the water, storing them in sediments and fostering sediment accretion and carbon burial. Mangrove ecosystems have declined over the past five decades, largely due to aquaculture. This decline reduces coastal resilience, exacerbating risks from storms, sea-level rise, and erosion, while releasing stored carbon as CO2 emissions. Mangrove degradation is crucial for climate mitigation. Mitigation strategies should prioritize conserving ecosystems with high carbon sequestration rates, reducing anthropogenic CO2 emissions, and rehabilitating mangrove habitats converted for aquaculture. We must expand our knowledge and understanding of the significance of mangroves in delivering coastal protection, how mangrove ecosystems serve as carbon sinks, how future changes could impact them, and how anthropogenic activities and climate change can impact their carbon storage.